Tricks and treats - Murphy, Stephen; Spaziante, Patrick (New York: Simon Spotlight, 2004)
It's Halloween, and when the Turtles find out that the Purple Dragons have stolen candy from a bunch of kids, its time for some scary ninja tricks to get back all those treats.
"Based on the TV series Teenage Mutant Ninja Turtles as seen on Fox and Cartoon Network"--T.p. verso.
Keywords: Teenage Mutant Ninja Turtles (Fictitious characters); Halloween; Halloween costumes; Heroes